Clinical, humanistic, and economic burden of sickle cell disease in The Jazan Region, Saudi Arabia - Abdulkarim M. Meraya; Otilia J. F. Banji; Santhosh Joseph Menachery; Hafiz Mosa Ali Malhan; Hatim Ali Asiri Halawi; Dhaifallah Moraya; Hamad Ahmed Hakami; Abdulaziz Mohammed Kubayni; Yunus Yahya Alfaifi; Hafiz Ibrahim Ghareeb; Mohammed Ali Abu Rasayn; Rayan Ahmed Alfaifi (PLoS ONE, 2026)
Background Sickle cell disease (SCD) constitutes a significant public health concern in the Kingdom of Saudi Arabia (KSA), affecting a substantial proportion of the population in the southern province of Jazan. The chronic and progressively incapacitating nature of SCD exerts a humanistic, psychological, and economic burden on the affected individuals and families. This study aims to assess this multifaceted burden on individuals with SCD in the Jazan region of KSA. Methods We conducted a cross-sectional observational study using a self-administered validated questionnaire among SCD patients seeking medical services in various hospitals in the Jazan region. The questionnaire included sections to assess physical health, pain, social life, psychological distress, and financial burden. Descriptive statistics summarised participant characteristics. Comparative analyses using Chi-square tests and T-tests were conducted to explore differences in demographic variables between respondents reporting higher versus lower spending burdens. These analyses were intended to describe observed differences within the study sample rather than to infer population-level associations. Results We included 110 individuals with SCD, with a mean age of 28.43 ± 9.66 years, 55.5% male, 4.5% non-Saudi, single (62.7%), with a little less than half residing in cities. The study showed low employment rates (36.4%) and high out-of-pocket expenditures for over half the patients, with transportation being the largest expense (SAR 828.51 ± 925.84/USD 220.94 ± 246.89 per month). High spending burden was associated with poorer physical health ( p < 0.001). Hydroxyurea was the most commonly used therapeutic option (81.8%), while the use of newer agents, such as L-glutamine and crizanlizumab, was limited. Psychological distress was significantly associated with age ( p = 0.008) and marital status ( p = 0.001), with married individuals being more distressed. Social scores ( p = 0.006) were significantly lower in individuals experiencing distress, while physical health ( p < 0.001) and pain scores were higher ( p < 0.001). Most reported disruption in social interactions and work life, compounded by a lack of family support. Furthermore, a majority felt their physicians lacked empathy and did not discuss treatment goals, necessitating half to avoid visits due to fear. Conclusion SCD patients face considerable socioeconomic, psychological, and healthcare challenges, with out-of-pocket costs disproportionately burdening lower-income families. Individuals with SCD reported psychological distress, social disruption and reduced quality of life. An apparent variability in professional and familial support was noted, which may have contributed to differences in health care utilization. Additionally, self-reported quality of physician-patient communication and perceived empathy were identified as potential influences for their care-seeking behaviour. These findings reinforce the need for a larger-scale, comprehensive evaluation to confirm them and assess the need for interventions to improve healthcare access and address the psychosocial and economic burdens associated with SCD.